COUNSELOR PROFESSIONAL IDENTITY OF COUNSELOR PROFESSION EDUCATION - Farozin, Muh (Jurnal Cakrawala Pendidikan, 2019)
This paper describes professional identity of counselor educators teaching in a counselor profession education in Indonesia. The counselor identitiy was explored using a self-reported semi-open questionnaire and a focus-group discussion. Using the questionnaire, the couselors self-assessed their competency level of 75 competence-statement based on the government's regulation. Their self-assessed level of competencies was compared to factors like age, teaching experiences, professional development as well as their self-efficacy toward the counselor competencies mandated by the government. To confirm the survey findings, a focus-group discussion was held and revealed culture-specific competencies that were not explicated in the regulation but deemed an important characteristic of the counselors' identity. The study found that the counselors described themselves having average level of the mandated competencies and developing culture-specific competency related to technology literacy. The findings provide recommendation to set up context-suited professional development training that prepare the counselors for teaching in the profession training.